2017
DOI: 10.1016/j.ydbio.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Celsr1 coordinates the planar polarity of vestibular hair cells during inner ear development

Abstract: Vestibular hair cells of the inner ear are specialized receptors that detect mechanical stimuli from gravity and motion via the deflection of a polarized bundle of stereocilia located on their apical cell surfaces. The orientation of stereociliary bundles is coordinated between neighboring cells by core PCP proteins including the large adhesive G-protein coupled receptor Celsr1. We show that mice lacking Celsr1 have vestibular behavioral phenotypes including circling. In addition, we show that Celsr1 is asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…2E,F and Shima et al (2002)]. Consistent with this expression, CELSR1, FZD3 and VANGL2 proteins are enriched at boundaries between hair cells and supporting cells throughout the organ of Corti (Curtin et al, 2003;Duncan et al, 2017;Montcouquiol et al, 2006;Wang et al, 2006b), and mutations in Celsr1, Fzd3 and Vangl2 result in mis-oriented stereociliary bundles (Curtin et al, 2003;Montcouquiol et al, 2003;Wang et al, 2006b).…”
Section: Type II Sgn Peripheral Axons Make Stereotyped Turns Towards mentioning
confidence: 63%
See 1 more Smart Citation
“…2E,F and Shima et al (2002)]. Consistent with this expression, CELSR1, FZD3 and VANGL2 proteins are enriched at boundaries between hair cells and supporting cells throughout the organ of Corti (Curtin et al, 2003;Duncan et al, 2017;Montcouquiol et al, 2006;Wang et al, 2006b), and mutations in Celsr1, Fzd3 and Vangl2 result in mis-oriented stereociliary bundles (Curtin et al, 2003;Montcouquiol et al, 2003;Wang et al, 2006b).…”
Section: Type II Sgn Peripheral Axons Make Stereotyped Turns Towards mentioning
confidence: 63%
“…The role of PCP signaling in development of the mammalian ear is well established, particularly for the sensory receptor hair cells where core PCP proteins are required to coordinate the orientation of polarized stereociliary bundles between neighboring cells (Copley et al, 2013;Curtin et al, 2003;Duncan et al, 2017;Montcouquiol et al, 2003;Stoller et al, 2018;Wang et al, 2006a;Yin et al, 2012). Given the striking morphological similarities between commissural neurons and type II SGNs, and the role of PCP signaling in both commissural axon guidance and inner ear development, we hypothesized that PCP could similarly direct type II SGN development.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Ghimire et al, 2018). Furthermore, turning errors are prevalent in the CELSR1 KO cochlea in which IHC and OHC stereociliary bundle orientation is normal (Duncan et al, 2017). Last, selective deletion of Vangl2 from supporting cells using FGFR3-iCreER is sufficient to induce a high frequency of turning errors (Ghimire et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway has been extensively studied in Drosophila as it controls the chirality of ommatidia and the polarity of cuticular hairs and bristles (15,20,21). In mice, PCP controls the normal orientations of multiple anatomic structures, including hair follicles and hair-associated appendages in the skin (22)(23)(24)(25)(26), stereocilia bundles of inner ear sensory hair cells (27)(28)(29)(30) and motile cilia in the trachea, cerebral ventricle and oviduct (31)(32)(33)(34)(35). Studies in Drosophila and mammals have identified a core set of three membrane proteins that regulate PCP: the seven-pass transmembrane protein Frizzled (Fzd), the four-pass transmembrane protein Strabismus (Stbm, Vangl in mammals) and the seven-pass transmembrane atypical cadherin Flamingo (Fmi, Celsr in mammals).…”
Section: Planar Cell Polarity and Astn2mentioning
confidence: 99%